SWOT Analysis in Preparing Company Strategic Plans - Barja, Riky (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2024)
Effective business strategy requires a deep understanding of the strengths, weaknesses, opportunities and threats that exist in the market. In facing a dynamic business environment, companies need to utilize their internal strengths to take advantage of external opportunities, while simultaneously overcoming their weaknesses to face existing threats. Flexibility, adaptability, good communication, and social and environmental responsibility are also key elements in a successful business strategy. With a holistic and sustainable approach, companies can achieve sustainable growth and strengthen their position in the market.